A Proposed Public Key Encryption Based on Hybrid Chaotic Maps - Ahmed T. Sadeeq; Alaa K. Farhan; Shaimaa A. Hassan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Cryptography has long history by providing a way to store sensitive information or transmit it across insecure networks (i.e. the Internet) so that it cannot be read by anyone except the intended recipient. Because data transmitted over the network is vulnerable to attack, it must be considering the security aspect of it. In this paper, a public key encryption algorithm based on hybrid chaotic maps is proposed. The proposed algorithm uses a mixing of three dimensional Logistic map, three dimensional Arnold Cat map, two dimensional Rotation Equation and Chebyshev map to set random values to this algorithm and to generate privet and public keys that are used to encrypt and decrypt data. The experimental results show that the generated keys have the characteristics of truly random numbers and pass most of statistical and NIST tests.